1974
DOI: 10.1159/000231210
|View full text |Cite
|
Sign up to set email alerts
|

No Evidence for an Immunological Cross-Reaction between Encephalitogenic Myelin Basic Protein and Histones

Abstract: An immunological cross-reaction between histones and the encephalitogenic myelin basic protein (MBP) of brain white matter has been discussed repeatedly. The binding ability of the histones Fl, F2a1, F2a2, F2b and F3, isolated from calf thymus, and of the F2c fraction of chicken erythrocytes to antibodies against human MBP was examined using a radioimmunological technique with high sensitivity. There was no evidence for any immunological cross-reaction between these closely related basic proteins, neither by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1976
1976
1981
1981

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Indirect evidence, in support of Johns' data, has been recently provided by Sabolovic et al (1975) who showed that massive agglutination of cancer patients' lymphocytes occurred in the presence of histone fraction 2a1, but that lymphocytes from normal volunteers were unaffected. However, conflicting information has been published by Schmid et al (1974) who were unable to demonstrate immunological cross-reactivity between histone fractions 1, 2a1, 2a2, and 3 to antibodies directed against human myelin basic protein. Although the lack of crossreactivity of the histone fractions to antibodies directed against myelin basic protein supports our findings, it has been argued that T-cell receptors may not recognize the same determinants as B-cell immunoglobulins (Diener and Langman, 1975).…”
mentioning
confidence: 99%
“…Indirect evidence, in support of Johns' data, has been recently provided by Sabolovic et al (1975) who showed that massive agglutination of cancer patients' lymphocytes occurred in the presence of histone fraction 2a1, but that lymphocytes from normal volunteers were unaffected. However, conflicting information has been published by Schmid et al (1974) who were unable to demonstrate immunological cross-reactivity between histone fractions 1, 2a1, 2a2, and 3 to antibodies directed against human myelin basic protein. Although the lack of crossreactivity of the histone fractions to antibodies directed against myelin basic protein supports our findings, it has been argued that T-cell receptors may not recognize the same determinants as B-cell immunoglobulins (Diener and Langman, 1975).…”
mentioning
confidence: 99%
“…Thus, the method of separating the immune complex is optional: from the double-antibody method of Driscoll et al (1974a), Whitaker and McFarlin (1977), or Palfreyman et al (1978); the ethanol method of Cohen et al (1975) and of Brostoff et al (1974); the gel filtration method of McPherson and Camegie (1968) as used by Lennon and Mackay (1972) and by Bemard and Camegie (1975); the dextran-<:harcoal method of Schmid et aL (1974); or the sodium-sulfate-modified Fan technique of Day and Pitts (1974a) as also used by , Randolph et al (1977), and Wallace et al (1978). Whitaker and McFarlin (1977) have addressed this point and show very clearly that when different methods for analyzing MBP are used at comparable concentrations of antigen and antibody, the method of separating the immune complex from the free form is immaterial to the outcome of the assay.…”
Section: Mbp As a Multideterminant Self-antigen In Humoral Immunmentioning
confidence: 99%
“…Although these problems have been discussed in detail elsewhere , it should be obvious that measuring an ABC at 167 (Driscoll et al, 1974a), 148 (Day and Pitts, 1974b), 10 (Whitaker and McFarlin, 1977), 2.2 (Lennon et al, 1971),1.67 (Day et al, 1978b), or 0.003 nM MBP (Schmid et al, 1974) could not possibly capture the same antibody populations with the same average binding affinity against the same MBP determinants. Conclusions drawn from reactions at one affinity, therefore, would not necessarily hold for another.…”
Section: Mbp As a Multideterminant Self-antigen In Humoral Immunmentioning
confidence: 99%